Bronchoscopic management of prolonged air leak - Keshishyan, Sevak (J Thorac Dis, 2017)
Bronchopleural fistula (BPF) with prolonged air leak (PAL) is most often, though not always, a sequela of lung resection. When this complication occurs post-operatively, it is associated with substantial morbidity and mortality. Surgical closure of the defect is considered the definitive approach to controlling the source of the leak, but many patients with this condition are suboptimal operative candidates. Therefore there has been active interest for decades in the development of effective endoscopic management options. Successful use of numerous bronchoscopic techniques has been reported in the literature largely in the form of retrospective series and, at best, small prospective trials. In general, these modalities fall into one of two broad categories: implantation of a device or administration of a chemical agent. Closure rates are high in published reports, but the studies are limited by their small size and multiple sources of bias. The endoscopic procedure currently undergoing the most systematic investigation is the placement of endobronchial valves. The aim of this review is to present a concise discussion on the subject of PAL and summarize the described bronchoscopic approaches to its management.